2008
DOI: 10.1128/aem.02450-07
|View full text |Cite
|
Sign up to set email alerts
|

Factors Controlling the Distribution of Archaeal Tetraethers in Terrestrial Hot Springs

Abstract: Glycerol dialkyl glycerol tetraethers (GDGTs) found in hot springs reflect the abundance and community structure of Archaea in these extreme environments. The relationships between GDGTs, archaeal communities, and physical or geochemical variables are underexamined to date and when reported often result in conflicting interpretations. Here, we examined profiles of GDGTs from pure cultures of Crenarchaeota and from terrestrial geothermal springs representing a wide distribution of locations, including Yellowsto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
113
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 59 publications
13
113
0
1
Order By: Relevance
“…These results are in good agreement with a previous study of globally distributed soils by Weijers et al (2006b), showing that the relative abundance of crenarchaeol in soils was higher with increasing pH values. Pearson et al (2008) also showed that the abundance of crenarchaeol occurring in terrestrial hot springs was positively correlated with pH. However, Nicol et al (2008) showed that autotrophic archaeal ammonia oxidation occurred predominantly in acid soils and that the abundance of ammonia-oxidizing Crenarcheota decreased with increasing soil pH values.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in good agreement with a previous study of globally distributed soils by Weijers et al (2006b), showing that the relative abundance of crenarchaeol in soils was higher with increasing pH values. Pearson et al (2008) also showed that the abundance of crenarchaeol occurring in terrestrial hot springs was positively correlated with pH. However, Nicol et al (2008) showed that autotrophic archaeal ammonia oxidation occurred predominantly in acid soils and that the abundance of ammonia-oxidizing Crenarcheota decreased with increasing soil pH values.…”
Section: Discussionmentioning
confidence: 99%
“…The GDGT composition of the cultured thermophilic AOA Nitrosocaldus yellowstonii and members of Crenarchaeota vary with pH (20,(45)(46)(47). However, for the highly buffered ocean, pH variability is relatively small, and thus would not be expected to significantly bias reconstructed SST.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these genes derive from archaea within the Great Basin hot spring crenarchaeal cluster I (GBSHSC1), which was designated to describe the dominant archaeal 16S rRNA genes recovered from several 56 to 67°C spring systems in the Great Basin, including Surprise Valley (13). The Surprise Valley and Eagleville samples that were the source for cluster A1.1 amoA alleles also contained a preponderance of crenarchaeol relative to other GDGTs (28,29,44). However, in the absence of a pure or highly enriched culture of GBSHSC1, amoA gene alleles from these springs cannot be linked definitively to either 16S rRNA phylotypes or particular membrane lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Similar amoA genes were amplified using PCR from hot spring sediment samples from a variety of Yellowstone springs (5). In culture, the pre-dominant membrane lipid of "Candidatus Nitrosocaldus yellowstonii" was the glycerol dialkyl glycerol tetraether (GDGT) crenarchaeol, confirming a thermophilic source for crenarchaeol in hot spring environments (28,29,34,44). Finally, a third study coupled rate measurements of complete nitrification by the 15 NO 3 Ϫ isotope pool dilution approach in two 84 to 85°C hot springs in Iceland, with the identification of crenarchaeol in one hot spring (30).…”
mentioning
confidence: 99%